Anti‐Corrosion for Reversible Zinc Anode via a Hydrophobic Interface in Aqueous Zinc Batteries. Issue 9 (15th January 2022) - Guan, Kailin; Tao, Li; Yang, Rong; Zhang, Haonan; Wang, Nengze; Wan, Houzhao; Cui, Jian; Zhang, Jun; Wang, Hanbin; Wang, Hao
Abstract: Water corrosion and dendrite growth seriously break the zinc plating/stripping process at the electrolyte/anode interface, causing the instability of the zinc metal anode of aqueous zinc batteries. Herein, a self‐consistent hydrophobic interface and orderly channels are assembled by three quaternary ammonium cationic surfactants, which can block the water erosion. Of particular interest, experimental results combined with theoretical calculation (DFT) reveals that the hydrophobic groups in quaternary ammonium cations are the determinaning factor in the kinetic process of zinc ion deposition and the life of the zinc anode. The massive micelles formed by benzyldimethyldodecylammonium with dodecyl and benzyl groups cause great hindrance to the transport and deposition of zinc ions. And dodecyltrimethylammonium with only a main hydrophobic group of dodecyl results in the higher polarization overpotential or voltage hysteresis for the zinc plating and lower coulombic efficiency (CE) < 99%. Surprisingly, the hydrophobic interface assembled by benzyltrimethylammonium (TMBA + ) with a main benzyl group can inhibit side reactions and regulate zinc uniform deposition. And the batteries based on TMBA + can achieve superb cycle stability with low voltage hysteresis and almost 100% CE. The proposed hydrophobic interface formed by quaternary ammonium cationic surfactants establishes pioneering work on zinc anode stability for zinc batteries and beyond. Abstract : Reversibility and anti‐corrosion for a zinc metal anode are realized by a self‐consistent hydrophobic interface assembled using quaternary ammonium cationic surfactants as additives in an aqueous electrolyte. The regulatory mechanism of different hydrophobic groups on the adsorption behavior of cationic additives and the kinetic process of zinc deposition are illuminated. Excellent long‐term stable aqueous zinc batteries is obtained.